Pedestrian Mobility for Urban Growth : Walking and its Links to Transportation - World Bank Group (World Bank, Washington, DC, 2019)
African cities are growing faster than cities on any other continent. With populations growing at such an enormous rate, it is often difficult for infrastructure to keep pace with urban growth. Rising automobile traffic on the continent has posed a great challenge. Increasingly, African cities struggle to handle the volume of motor vehicle traffic on their roadways. African urban dwellers spend much of their time stuck in traffic and away from their work and families. Public transport systems and pedestrian facilities must be improved so that African cities may continue to grow without suffering the consequences of runaway growth in private vehicle traffic. This report includes case studies of the institutional structures, financing practices, and regulations that have been adopted by cities and have been successful at achieving dramatic improvements in the design and implementation of the pedestrian environment. The report draws on international best practice and pilot projects in Africa to provide guidance on the key elements that should be considered in the design and maintenance of high-quality walking environments.